LEARNING INDEPENDENCE OF JUNIOR HIGH SCHOOL STUDENTS THROUGH THE USE OF RADEC LEARNING MODEL IN SCIENCE LEARNING - Juita, Dewi; Yusmaridi, Yusmaridi (Department of Science Education, 2024)
The purpose of this study was to determine the description of students' learning independence after using the RADEC (Read, Answer, Discuss, Explain, Create) learning model in learning science in energy material. This research was analyzed using a quantitative approach with descriptive methods. The instrument used to measure students' learning independence is a learning independence questionnaire using positive statements. The learning independence of students has been achieved by 26 students with a percentage of 87%. Learners who do not depend on others as much as 83%, are responsible for their duties as much as 83%, have 93% self-confidence, have 87% discipline, act on their own initiative as much as 90%, and are able to control themselves as much as 83%.